Economic Analysis of The Underground Coal Gasification (UCG) in Indonesia - Kurnia Hudaya, Gandhi; Tjendrasa, Kin (The Indonesian Journal of Business Administration, 2018)
Abstract. The demand for primary energy, especially electricity in Indonesia is increasing. Indonesia’s economy has been depended on natural resources as the second main contributor of country’s income. Indonesia is still depended on fossil fuels, especially on oil and gas. Indonesia’s consumption of oil have been exceeded its production since year 2004. There is big possibility that Indonesia need to import gas in 2021 due to the supply is not sufficient. It means that Indonesia new reserves is very important to be found either from conventional gas or unconventional gas.  Indonesia not only has oil and gas but also coal which its resources is quite abundant. There is deep seated coal potency with depth >100 meter below surface in Indonesia that has not been exploited yet. Underground Coal Gasification (UCG) is an unconventional technology that can become the solution to exploit the deep seated coal potential. UCG can be applied  for extracting coal into in-situ gas directly in the underground layers without excavation of rock cover and coal seam first. The objective of this paper is to make economic analysis regarding the implementation of underground coal gasification (UCG) technology in Indonesia. Data are collected from literature, expert and pilot plant in South Sumatra.  From the result of the economic analysis, it can be concluded that UCG project is very potential to be developed in Indonesia. The result of economic indicators are that NPV is $27,069,000,-, IRR is 14% and the payback period is 7 years. Sensitivity analysis on UCG project shows that the project is more sensitive to capital expenditure and electricity selling price and less sensitive to drilling cost, corporate tax rate and coal royalty.Keywords : UCG, economic analysis, deep seated coal